Special Dio 3-Tuples Involving Octagonal Pyramidal Numbers - C. Saranya; G. Janaki; R. Janani (Explorations in Diophantine Equations, 2023)
This chapter tries to build special Dio 3-tuples that satisfy the property that the product of any two of the triple’s members subtracted by a non-zero integer or a polynomial with integer coefficients is a perfect square. The special Dio 3-tuples from octagonal pyramidal numbers of various ranks are also presented in each of the three parts along with the relevant features.